Peptide microarrays enable rapid mimotope optimization for pharmacokinetic analysis of the novel therapeutic antibody IMAB362. Issue 4 (7th March 2014) - Schnatbaum, Karsten; Schmoldt, Hans‐Ulrich; Daneschdar, Matin; Plum, Laura M.; Jansong, Janina; Zerweck, Johannes; Kühne, Yvonne; Masch, Antonia; Wenschuh, Holger; Fiedler, Markus; Türeci, Özlem; Sahin, Ugur; et al.
Abstract As membrane proteins play an important role in a variety of life‐threatening diseases, the development of therapeutic monoclonal antibodies against membrane proteins is of significant interest. Among many other requirements, the process of antibody drug development requires a set of tailor‐made assays for the characterization of the antibodies and for monitoring their activity. Designing assays to characterize antibodies directed to membrane proteins is challenging, because the natural targets are often not available in a format that is compatible with a biochemical assay setup. Thus, alternatives that mimic the targeted membrane proteins are needed. In this study, we developed optimal peptidic mimotopes for the ELISA‐based detection of the novel therapeutic antibody IMAB362 in biological samples. Initial hits were identified using phage display and these hits were optimized with the help of structure‐activity relationship analysis on peptide microarrays. The optimized peptides showed binding constants in the low nanomolar to picomolar range, an improvement by a factor of up to 30 compared to the initial hits. The best mimotope (apparent KD = 0.15 nM) was successfully used for the ELISA‐based quantification of IMAB362 in samples from a mouse pharmacokinetic study. The process described allows the rapid discovery of mimotopes for target proteins that are difficult to produce or handle, which can then be used in pre‐clinical and clinical assays or for the purification of biological products.